Trust, Justice, Ethics Dan Job Performance dalam Perspektif Islam Pada Tenaga Kependidikan Institut Agama Negeri (IAIN) Bengkulu - Khairiah Khairiah (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2019)
The article is to depict trust, justice, and ethics to the job performance in Islamic perspective on educational staffs of the State Islamic Institute (Institut Agama Islam Negeri - IAIN) of Bengkulu. This research design using qualitative descriptive method is data collection using a set of instruments; namely interviews, observation and documentation. The results show that trust, justice, ethics in Islamic perspective can improve job performance. It is advisable if one wants to improve the job performance; then, there should be increase the trust, justice, and ethics at the educational staff of the State Islamic Institute Bengkulu.